Automated insulin delivery for safe fasting and exercise during Ramadan in patients with type 1 diabetes: The active fast study - Khaled Baagar (7487690) (2025)
Aims To evaluate the safe and effective use of the MiniMed™ 780G Advanced Hybrid Closed-Loop system (AHCLS) in adults with type 1 diabetes mellitus (T1DM) during Ramadan fasting combined with structured Moderate-Intensity Exercise (MIE) followed by the non-fasting month (Shawwal) with continued MIE. Methods This prospective, single-arm interventional study recruited 34 adults with T1DM using the MiniMed™ 780G. Participants performed MIE during non-fasting hours in Ramadan and continued it in Shawwal. Analyzed parameters included glycemic control, insulin requirements, usage of the MiniMed™ 780G system, metabolic parameters, and treatment satisfaction. Results Median time below range (<70 mg/dL) remained stable (1.0 %) across Ramadan and Shawwal (p = 0.39). Time in range (70–180 mg/dL) was significantly higher during Ramadan (70.5 %) than Shawwal (68.5 %, p = 0.0134), with a less median time above range(>180 mg/dL) in Ramadan (29 %) compared to Shawwal (30 %) (p = 0.0088). No severe hypoglycemia or DKA occurred. Participants demonstrated high treatment satisfaction and SmartGuard mode usage, with good adherence to fasting and exercise. Conclusions Adults with T1DM can safely fast during Ramadan and exercise using the MiniMed™ 780G to manage diabetes. Findings from this study build on the real-world evidence to enhance clinical guidelines for optimal T1DM care using advanced technology. Other Information Published in: Diabetes Research and Clinical Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.diabres.2025.112353